车用复合无级变速器行星排组拓扑分析 - 杨凌; 黄向东; 罗玉涛; 赵克刚; 黄河 (Jixie chuandong)
A new type of composite CVT（Continuously Variable Transmission） systems,based on dual-mode power-split planetary gear set,is of improved efficiency,power transmutability and speed variable range.On the basis of its working principles and feasible methodology,36 alternative topologies of the dual-mode planetary gear sets have been comparatively analyzed in detail,and a few topologies suitable for automotive applications has been finally chosen and recommended.